INOVASI PRODUK OLAHAN PERIKANAN TINGGI PROTEIN SEBAGAI CAMILAN SEHAT DAN BERNILAI EKONOMI TINGGI - Maria Magdalena N.M Tukan; Maria Hermina Peransa Betan (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Snacks are a type of food consumed outside of main meals and play a role in helping meet daily calorie needs. However, most snacks on the market today contain monosodium glutamate (MSG), calories, fat, and other additives that are potentially harmful to health. Therefore, innovation is needed in creating snacks that are not only delicious but also highly nutritious. One effort that can be done is by adding animal protein sources, such as skipjack tuna, which is known for its high protein content and good nutritional value. This activity aims to improve the skills of the community, especially micro-business owners, in processing skipjack tuna into economically valuable snack products. The method used in this activity is direct practice or demonstration of making various processed skipjack tuna products. The training process begins with preparing the main ingredient, namely skipjack tuna meat, then continues with mixing complementary ingredients, processing, and packaging the final product. The results of the activity showed that the resulting snack products, such as fish floss, fish sticks, and fish crackers, are of satisfactory quality. Training participants assessed the process as easy to make, the ingredients are economical, and the products can be stored for a long time. Furthermore, these processed products have good sales potential, making them a source of additional income for families. In conclusion, the training on producing skipjack tuna snacks not only improves the community's skills in processing local food ingredients but also contributes to the development of micro-enterprises and the diversification of highly nutritious food products within the community.